Catholicism in Italy in the Age of Pluralism. (Lexington Books, 2012)
Public interest in religious institutions and 'religious' phenomena in Italy has been on the rise, with the surge of debates and studies regarding religion and national identity, religion and its historical role, and religion and civil values. In Catholicism in Italy in the Age of Pluralism, Franco Garelli presents an interesting perspective and analysis of the controversial and ambivalent dynamics that characterize the dialogue on religion and politics within Italy today.